Robinsons Children's Library, Inc.-Imus, Cavite provider of library services to children - Cruz, Fraymon Joy P. (2005)
This study assessed the case of Robinsons Children's Library, Inc. (RCLI)-Imus RCLI as provider of services to children. The general purpose fo this study was to assess the RCLI-Imus, Cavite as provider of services to children with the children as respondents. There are 500 library users of the Children's Library Inc.-Imus Branch who were given the said questionnaires. All of them returned the questionnaires. This is equivalent to 100 percent of the sample population.